Augmented reality marketing: enhancing customer experience through latest technology - Ismail Razak (Jurnal Multidisiplin Sahombu, 2024)
Recent technological developments, especially AR, have opened up new opportunities for companies to innovate in their marketing strategies. This research will focus on how the integration of AR in marketing campaigns can create more immersive, interactive and memorable consumer experiences. This research uses a qualitative approach with descriptive methods. The research results show that the application of Augmented Reality (AR) in marketing, user experience and education has a significant positive impact. In marketing, AR creates more immersive interactive experiences, increases consumer engagement, and adds value to marketing campaigns. The use of personalization in the user experience through AR increases the relevance of content, creating deeper interactions between brands and consumers. On the educational side, AR provides an additional visual dimension to learning, facilitating better understanding of concepts. Overall, the research results confirm that AR is not only an innovative technology, but also an effective tool for enriching and improving the way we interact with information, brands, and learning.